“UKRAINIAN SACRED MUSIC” ELECTRONIC STUDU GUIDE: CONTENT, STRUCTURE, USE RECOMMENDATIONS AT A PEDAGOGICAL HIGHER EDUCATION INSTITUTION (Journal of Information Technologies in Education (ITE), 2014)
The article presents the electronic textbook “Ukrainian Sacred Music”, created for the students of pedagogical universities – future teachers of music. We consider the content of the electronic manual, its structure, requirements for the computer, as well as the prospects for its use in the classroom on the history of Ukrainian music and self-study.
Keywords: Ukrainian sacred music; electronic textbook; content; structure